A comparison of tuberculous and bacterial native joint septic arthritis infections in a retrospective cohort: Presentation characteristics, outcomes and long term follow up. (January 2022) - William Goodall, Jack; James Patterson, Benjamin; Barrett, Jessica; Colquhoun, Matthew; Williamson, Sarah; Clayton-Smith, Ana; Koh, Gavin; Corrah, Tumena
Highlights: Patients with bacterial versus tuberculous septic arthritis had significantly higher CRP levels and neutrophil counts. A CRP level above 100 mg/L conferred an odds ratio of 46 for bacterial infection. 51% of bacterial septic arthritis cases were asymptomatic at last follow up compared to 72% of tuberculous cases. Abstract: Objectives: This retrospective observational cohort study aimed to characterise and compare the demographics, initial laboratory tests and outcomes between patients with large-joint bacterial septic arthritis (BSA) and tuberculous septic arthritis (TBSA). Methods: All patients with a culture from a large, native joint growing either non-mycobacterial bacteria or Mycobacterium tuberculosis between 1 January 2012 and 1 October 2018 in our institution were included. Clinical details and admission laboratory values were obtained from patient records. Comparisons were made by Mann-Whitney U, chi-squared tests, and logistic regression analysis. Results: We identified 64 BSA and 29 TBSA. On average, the BSA cases were older, had higher CRP levels and neutrophil counts and lower albumin levels. The odds ratio for having a BSA was 46 in cases with a CRP greater than 100 mg/L (95% confidence interval (CI) 8.5–850, p < 0.001) and 24 with a neutrophil count greater than 7.5x10 9 (95% CI 6.1–160, p < 0.001). 51% of BSA were asymptomatic at last follow up compared to 72% of TBSA. 14% of the BSA cases died during admission; there were no deaths in the TBSA group. Conclusions: Significant differences exist between patients with BSA and TBSA. Whilst no test is sufficient to exclude BSA, a raised neutrophil count or a CRP greater than 100 mg/L significantly increases the odds of a bacterial aetiology. Patients with BSA had worse long-term outcomes and higher incidence of inpatient mortality.